The Impact of customer relationship and the ability to value-added service in the performance of manufacturing SMEs in Aguascalientes - Gabriela Ortiz-Delgadillo; Edgar Omar Esquivel-Aguilar; Octavio Hernández-Castorena (Revista CEA, 2017)
This research was conducted to know the impact of customer relationships and the ability to add value to the service on the performance of the Management Supply Chain SMEs in the State of Aguascalientes. For this, a quantitative study was conducted with correlational scope, crosssectional, in which an instrument Likert scale Such measurement is built, is composed of 27 items, divided into 3 main blocks: Relationship with customers (16 items), ability to add valueadded service (5 items) and performance (6 items). Which they were applied to a population of 213 entrepreneurs in the city of Aguascalientes. The data analysis was performed through the statistical technique of linear regression, for which made use of statistical software SPSS version 20, where the most significant results showed that the relationship with customers is fundamental to the SMEs to achieve higher performance in managing the supply chain.